2013
DOI: 10.3389/fcimb.2012.00171
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin-producing Escherichia coli in beef retail markets from Argentina

Abstract: Shiga toxin-producing Escherichia coli (STEC) are foodborne pathogens that cause mild or serious diseases and can lead to people death. This study reports the prevalence and characteristics of STEC O157 and non-O157 in commercial ground beef and environmental samples, including meat table, knife, meat mincing machine, and manipulator hands (n = 450) obtained from 90 retail markets over a nine-month period. The STEC isolates were serotyped and virulence genes as stx (Shiga toxin), rfbO157] (O157 lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 36 publications
2
39
3
4
Order By: Relevance
“…The results of the present study demonstrated that meat and meat products possess a high potential for causing human infection. Our findings indicated that 23.5% of minced beef samples were contaminated with STEC which was lower than that reported in previous investiga- tions in Iran (29.7%) and Argentina (52.5%) (Brusa et al, 2013) but higher than the result found in Switzerland (1.75%) and New Zealand (12%) (Brooks et al, 2001;Fantelli & Stephan, 2001). Considering the rising public health concern about non-O157 STEC, since 2012, Department of Agriculture (USDA)'s Food Safety and Inspection Service, expanded the zero tolerance policy for E. coli O157:H7 to include the top six non-O157 STEC serogroups in raw beef products (Wang et al, 2013).…”
Section: Discussioncontrasting
confidence: 76%
“…The results of the present study demonstrated that meat and meat products possess a high potential for causing human infection. Our findings indicated that 23.5% of minced beef samples were contaminated with STEC which was lower than that reported in previous investiga- tions in Iran (29.7%) and Argentina (52.5%) (Brusa et al, 2013) but higher than the result found in Switzerland (1.75%) and New Zealand (12%) (Brooks et al, 2001;Fantelli & Stephan, 2001). Considering the rising public health concern about non-O157 STEC, since 2012, Department of Agriculture (USDA)'s Food Safety and Inspection Service, expanded the zero tolerance policy for E. coli O157:H7 to include the top six non-O157 STEC serogroups in raw beef products (Wang et al, 2013).…”
Section: Discussioncontrasting
confidence: 76%
“…Ground beef contamination with STEC is a leading cause of dysenteric diarrhea foodborne outbreaks and HUS (Rivas et al, 2006;Werber et al, 2012). Countries in Latin America and Europe, in addition to the United States, have reported ground beef contamination with STEC (Brusa et al, 2012;Soborg et al, 2013;Robbins et al, 2014).…”
mentioning
confidence: 99%
“…A total of 20 STEC O157:H7 strains isolated in previous studies from butcher shops were studied (Brusa et al, 2012;Brusa et al, 2015). The samples were collected between 2010 and 2013 from the city of Berisso, which has 135 km 2 and 83,123 inhabitants.…”
Section: Bacterial Strainsmentioning
confidence: 99%